Optimal Taxation of Capital Income with Heterogeneous Rates of Return - Aart Gerritsen; Bas Jacobs; Alexandra V. Rusu; Kevin Spiritus (Tinbergen Institute, 2020)
There is increasing empirical evidence that people systematically differ in their rates of return on capital. We derive optimal non-linear taxes on labor and capital income in the presence of such return heterogeneity. We allow for two distinct reasons why returns are heterogeneous: because individuals with higher ability obtain higher returns on their savings, and because wealthier individuals achieve higher returns due to scale effects in wealth management. In both cases, a strictly positive tax on capital income is part of a Pareto-efficient dual income tax structure. We write optimal tax rates on capital income in terms of sufficient statistics and find that they are increasing in the degree of return heterogeneity. Numerical simulations for empirically plausible return heterogeneity suggest that optimal marginal tax rates on capital income are positive, substantial, and increasing in capital income.
Keywords: H21; H24; 330; Optimal taxation; capital taxation; heterogeneous returns